The Influence of Online Sales Promotion on Purchasing Decision Factors at PT Heri Daya Integra Karawang - Azizah, Sintya; Army, Widya Lelisa; Rahayu, Tutik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research was conducted at PT Heri Daya Integra Karawang, with the aim of knowing the effect of sales promotion online and purchasing decision factors, as well as analysis of the influence of promotions in sales promotions online on purchasing decisions at PT Heri Daya Integra Karawang. The total number of research respondents was 60 people who were selected using Purposive Sampling techniques. This research explains that online sales promotions are included in the good category, as well as consumer purchasing decision factors that are included in the good category. Apart from that, there is the influence of sales promotions online on purchasing decision factors by consumers of PT Heri Daya Integra Karawang, and according to the calculation results seen in the table, a simple correlation coefficient of r = 0.880 and a determination coefficient of R = 12 = 0.774 are obtained. got Tcount (14.08) >Ttable (1.67) so it can be concluded that there is an influence between online sales promotions on purchasing decision factors. And there is a significant test on a simple relationship obtained if Fcount (198.18) > Ftable (4.00) on a = 0.05 and significance value (sig.) < 0.05 (0.00 < 0.05), it can be concluded that online sales promotions have a significant and linear influence on purchasing decision factors.